Evaluation of Preexisting Anti-Hemagglutinin Stalk Antibody as a Correlate of Protection in a Healthy Volunteer Challenge with Influenza A/H1N1pdm Virus - Jae-Keun Park (American Society for Microbiology, 2018)
ABSTRACT Influenza virus hemagglutinin (HA) surface glycoprotein is currently the primary target of licensed influenza vaccines. Recently, broadly reactive antibodies that target the stalk region of the HA have become a major focus of current novel vaccine development. These antibodies have been observed in humans after natural infection with influenza A virus, but the data are limited. Using samples and data from the uniquely controlled setting of an influenza A/H1N1 virus human challenge study of healthy volunteers, we performed a secondary analysis that for the first time explores the role of anti-HA stalk antibody as a human correlate of protection. An anti-HA stalk antibody enzyme-linked immunosorbent assay (ELISA) was performed on samples from 65 participants challenged with a 2009 H1N1pdm virus. Pre- and postchallenge anti-HA stalk titers were then correlated with multiple outcome measures to evaluate anti-HA stalk antibody titer as a correlate of protection. Anti-HA stalk antibody titers were present before challenge and rose in response to challenge in 64% of individuals. Those individuals with higher titers at baseline were less likely to develop shedding, but not less likely to develop symptoms. Similar to the hemagglutination inhibition (HAI) titer, the baseline anti-HA stalk antibody titer did not independently predict a decrease in the severity of influenza disease, while the antineuraminidase (neuraminidase inhibition [NAI]) titer did. As a correlate of protection, the naturally occurring anti-HA stalk antibody titer is predictive of a reduction of certain aspects of disease similar to HAI titer, but the NAI titer is the only identified correlate that is an independent predictor of a reduction of all assessed influenza clinical outcome measures. IMPORTANCE This is the first study to evaluate preexisting anti-HA stalk antibodies as a predictor of protection. We use a healthy volunteer influenza challenge trial for an examination of the role such antibodies play in protection. This study demonstrates that anti-HA stalk antibodies are naturally generated in response to an infection, but there is significant variability in response. Similar to antibodies that target the HA head, baseline anti-HA stalk antibody titer is a correlate of protection in terms of reduced shedding, but it is not a predictor of reduced clinical disease or an independent predictor of disease severity. These results, in the context of the limited data available in humans, suggest that vaccines that induce anti-HA stalk antibodies could play a role in future vaccine strategies, but alone, this target may be insufficient to induce a fully protective vaccine and overcome some of the issues identified with current vaccines.